SISTEM INFORMASI E-KERJA PRAKTIK BERBASIS WEBSITE UNTUK OPTIMASI PROGRAM KERJA PRAKTK PADA PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA - Albert (2022)
In the modern era of the Industrial Revolution 4.0, almost all activities in human life are inseparable from information technology as a driver of other activities and services. With the development of the Industrial Revolution 4.0, various organizational activities, companies, and institutions have used information technology. The application of this technological development is an opportunity for the National Library of Indonesia to optimize the field practice work program through a website. This study aims to design and implement a website that can streamline practical work documentation such as practical work activities, activity reports, and the provision of e-certificates on a website. So that it makes it easy for students and employees in useful work programs. The research method used in this study uses Waterfall, which is more commonly known as the Classic Life Cycle. This study uses Black Box Testing to determine whether the system is running according to the expectations that have been designed and made accordingly. Based on the research results, this web design can help streamline the flow of registration for practical work programs which can be done online. The website not only provides registration facilities for prospective participants but when participants are accepted to carry out practical work, the website also assists participants in taking attendance, weekly reports, and E-Certificates which features are available on the website.